DOES EXPLICIT INSTRUCTION IMPROVE EFL STUDENTS’ READING COMPREHENSION? - Ni Luh Putu Ning Septyarini Putri Astawa; Ida Ayu Oka Purnami (Yavana Bhasha : Journal of English Language Education, 2023)
The aim of this study was to improve students’ reading comprehension using explicit instruction. Two-cycles classroom action research was applied in conducting this study. The study involved fourty-eight (48) 8th grade students of a private junior high school in Denpasar, Bali. In the process of collecting the data, the researcher administered pre-test and post-test to find the difference on students’ reading comprehension before and after being taught using explicit instruction method. A questionnaire was also administered in order to find out students’ response along the teaching and learning process. The results of this study indicate that explicit instruction could improve students’ reading comprehension significantly. It was also supported by the data of questionnaire that discovered students’ positive response on the method being used.